2017
DOI: 10.1002/chem.201701379
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Fusion of Liposomes by Nucleobase Quadruple‐Anchored DNA

Abstract: Anchoring DNA via hydrophobic units into the membrane of vesicles allows tagging of these nanocontainers with sequence information. Moreover, the hybridization of DNA on the surface of liposomes enables sequence specific functionalization, vesicle aggregation, and vesicle fusion. Specifically, DNA-hybridization-based approaches for fusion employing oligonucleotides terminally modified with one or two anchoring units were hindered by a limited degree of full fusion or by significant leakage during fusion. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 42 publications
0
47
0
Order By: Relevance
“…Numerous model systems for membrane fusion have been developed in recent years, all of which have employed a diverse range of molecules as fusogens. Examples of such fusogens include: hydrogen bonding motifs 1 , DNA [2][3][4][5][6][7][8][9][10][11] , PNA [12][13][14] , coiled-coil peptides [15][16][17][18] , and small molecule recognition motifs [19][20][21][22][23] . These systems exhibit varying efficiencies of fusion: some only facilitate hemifusion, or lipid-mixing; whereas others promote full fusion, resulting in content-mixing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous model systems for membrane fusion have been developed in recent years, all of which have employed a diverse range of molecules as fusogens. Examples of such fusogens include: hydrogen bonding motifs 1 , DNA [2][3][4][5][6][7][8][9][10][11] , PNA [12][13][14] , coiled-coil peptides [15][16][17][18] , and small molecule recognition motifs [19][20][21][22][23] . These systems exhibit varying efficiencies of fusion: some only facilitate hemifusion, or lipid-mixing; whereas others promote full fusion, resulting in content-mixing.…”
mentioning
confidence: 99%
“…We have previously developed a model system capable of specific, leakage-free, full fusion, which was inspired by SNARE-driven membrane fusion. This system comprises two coiled-coil-forming peptides named K 4 (KIAALKE) 4 and E 4 (EIAALEK) 4 24 , which serve as fusogenic recognition motifs. These are coupled to a cholesterol membrane anchor via a flexible polyethylene glycol (PEG) linker of variable length (Fig.…”
mentioning
confidence: 99%
“…Previous reports from our group showed that dodec‐1‐yne‐modified deoxyuridine nucleotides could be incorporated into common DNA sequences and that the resulting lipid DNA (U4T) could be anchored to phospholipid‐based liposome (1,2‐dioleoyl‐sn‐glycero‐3‐phosphocholine (DOPC), 1,2‐dioleoyl‐sn‐glycero‐3‐phosphoethanolamine (DOPE), and cholesterol) membranes in a straightforward manner . We here employed the fluorescence resonance energy transfer (FRET) method established in this previous work to prove the successful anchoring of lipid DNA U4T on the membrane of the liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…The lipid–DNA conjugates can be utilized to fuse liposomes, which were reported in two recent papers [53,54]. Kors and Herrmann reported the liposomes aggregation and liposomes fusion through the DNA hybridization.…”
Section: Small Molecules Modified Dnamentioning
confidence: 99%
“…The lipids of the DNA–lipids acted as the anchors into the liposomes, and the DNA sequences were anchored at the surface of liposomes to further hybridize with complement, resulting in membrane fusion. It is noteworthy that the number and position of lipids of the DNA–lipid conjugates could be precisely controlled by automated solid phase synthesis, and in the most efficient system, it achieved about 30% full fusion [53]. Using the similar strategy, Vogel group have systematically investigated the ability of lipid–DNA conjugates to mediate and control the programmable fusion of liposomes by DNA hybridization.…”
Section: Small Molecules Modified Dnamentioning
confidence: 99%